TINGKAT PEMAHAMAN GURU TERHADAP KARAKTERISTIK DAN PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) SMK NEGERI DI DIY - Maya Prabawati; Suparman Suparman (Universitas Negeri Yogyakarta, 2019)
ABSTRACT This study aims to determine the level of understanding of PKK teachers on the characteristics and application of the PjBL model in PKK learning on the construction and property technology expertise program of N SMK in DIY. This research is quantitative descriptive. The method used is a survey with data collection techniques using Guttmann's model questionnaire. Based on the results of the study, the PKK teacher's level of understanding of the characteristics and application of the PjBL model in PKK learning in the construction and property technology expertise program of DIY Vocational High Schools showed that there were 20 teachers (83.33%) in the